Influence of stratification and wind forcing on the dynamics of Lagrangian residual velocity in a periodically stratified estuary - Fangjing Deng; Feiyu Jia; Rui Shi; Shuwen Zhang; Qiang Lian; Xiaolong Zong; Zhaoyun Chen (Ocean Science, 2024)
Wind and stratification play pivotal roles in shaping the structure of the Lagrangian residual velocity (LRV). However, the intricate dynamics by which wind and stratification modify the LRV remain poorly studied. This study derives numerical solutions of LRV components and eddy viscosity subcomponents to elucidate the dynamics within the periodically stratified Pearl River estuary. The vertical shear cross-estuary LRV (uL) is principally governed by the interplay among the eddy viscosity component (uLtu), the barotropic component (uLba), and the baroclinic component (uLgr) under stratified conditions. During neap tides, southwesterly winds notably impact uL by escalating uLtu by an order of magnitude within the upper layer. This transforms the eastward flow dominated by uLtu under wind influence into a westward flow dominated by uLba in upper shoal regions without wind forcing. The along-estuary LRV exhibits a gravitational circulation characterized by upper-layer outflow engendered by a barotropic component (vLba) and lower-layer inflow predominantly driven by a baroclinic component (vLgr). The presence of southwesterly winds suppresses along-estuary gravitational circulation by diminishing the magnitude of vLba and vLgr. The contributions of vLba and vLgr are approximately equal, while the ratio between uLba and uLgr (uLtu) fluctuates within the range of 1 to 2 in stratified waters. Under unstratified conditions, LRV exhibits a lateral shear structure due to differing dominant components compared to stratified conditions. In stratified scenarios, the eddy viscosity component of LRV is predominantly governed by the turbulent mean component, while it succumbs to the influence of the tidal straining component in unstratified waters.